intermediate algebra
 👍 0
 👎 0
 👁 100

 👍 0
 👎 0
posted by drwls
Respond to this Question
Similar Questions

algebra
1. In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45 or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work when substituted back into the original
asked by Taina on June 20, 2011 
math
In solving the equation (x + 4)(x – 7) = 18, Eric stated that the solution would be x + 4 = 18 => x = 22 or (x – 7) = 18 => x = 11 However, at least one of these solutions fails to work when substituted back into the
asked by carol on May 4, 2011 
Algebra
In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45 or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work when substituted back into the original
asked by Sierra on October 13, 2011 
algbera
In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45 or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work when substituted back into the original
asked by kozy on May 1, 2011 
algebra
in solving the equation (x +2)(x  2) = 32 eric stated the solution to be x + 2 = 32 => x = 30 or x 2 = 32 => x = 34. however at least one of these solutions fails to work when plugged back into the equation. why is that? please
asked by Theresse on September 29, 2012 
South
In solving the equation (x + 1)(x – 2) = 54, Eric stated that the solution would be x + 1 = 54 => x = 53 or (x – 2) = 54 => x = 56 However, at least one of these solutions fail
asked by Nicole on February 16, 2011 
algebra
solving the equation (x+4)(x4)=9 Eric stated that the solution would be x+4=9>x=5 or (x4)=9=>x=13 However one of these solution fails to work when subsituted back to the original equation. Why?olve and explain the reasoning. Can
asked by mema on June 9, 2011 
Math
I don't understand how to solve this problem: In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work
asked by Angelina on August 22, 2011 
intermediate algebra
in solving the equation (x+4)(x4)=9 eric stated the solution would be x+4=9 =>5 or x4=9 =>13 however at least one of these solutions fails to work when subsituted back into the original equation. why is that? solve the problem
asked by Anonymous on August 22, 2012 
Math
In solving the eqaution(x+4)(x4),Eric stated thatthe solution would be x+4=33=>x=29 or (x4)=33=>x=37 However, at least one of these solutions fails to work when substituted back into the original eqaution. Why is that?Help Eric
asked by Sonya on February 16, 2011